Theatre of Donald Oenslager (Wesleyan University Press, 1978)
Donald Oenslager's working career spanned fifty years of the New York stage and during those years his influence extended across the country in the work of the many distinguished stage designers who had been his students at the Yale School of Drama. His autobiographical introduction to this book is, therefore, both a history of and a commentary on the theatre in New York from 1920 to the 1970s, and it admits us to the reflections of one of the most versatile artists who worked at the center of that development. This is a designer's book, and Donald Oenslager chose his subjects with a designer's eye. Over thirty-five productions are discussed in the light of the problems of interpretation and realization that they posed to the set designer. More than ninety illustrations illuminate Oenslager's mastery of the principles of design and his ability to exploit the technical possibilities of his theatre.